Генерирование испытательных импульсов магнитного поля - Петков, Александр Александрович (НТУ "ХПИ", 2006)
In article results of the analysis of forming properties of the pulsed generator of a magnetic field are given
Keywords: магнитное поле; генератор импульсов; форма импульса